A guide to formation advising for seminarians - McCormack, Edward J., 1960- (The Catholic University of America Press, 2020)
"Recent Vatican guidelines for seminary formation call for professional accompaniment of seminarians throughout their formation to become Catholic priests. This book lays out what these seminarians should expect from the entire formation process. Written by a veteran formator at a Roman Catholic seminary, it offers a practical guide to formation advising from the point of view of the men who will experience it. It includes a guide to and an example of the self-evaluation that is part of this process. The book contains an index and an annotated bibliography on the main areas of formation relevant to seminarians"--